THE EFFECT OF BUSINESS CAPITAL AND LABOR QUALITY ON THE SUCCESS OF MSME BUSINESSES - Larasati; Syafitri, Lili; Ratu, Mutiara Kemala (Transpublika Publisher, 2023)
This study aims to determine the effect of business capital and labor quality on the success of clothing sewing services in Ilir Timur I district, Palembang city. The research used a quantitative analysis method. The population in this study consisted of 186 business actors in clothing sewing services, and the sample used was 65 respondents, selected through simple random sampling. Primary data was collected through questionnaires distributed to clothing sewing service businesses in Ilir Timur I District, Palembang City. The data analysis technique used multiple linear analysis with the SPSS version 25 program. The results showed that both business capital and labor quality have a positive and significant influence on the success of clothing sewing services in Ilir Timur I District, Palembang City, either partially or simultaneously.